A Novel Real-time Video Transmission Approach for Remote Laboratory Development - Wang, Ning; Chen, Xuemin; Song, Gangbing; Parsaei, Hamid (International Journal of Online and Biomedical Engineering (iJOE), 2015)
Remote laboratories are an inevitable necessity for Internet enabled education in Science, Technology, Engineering, and Math (STEM) fields due to their effectiveness, flexibility, cost savings, and the fact that they provide many benefits to students, instructors and researchers. Accordingly, real-time experiment live video streaming is an essential part of remote experimentation operation. Nevertheless, in the development of real-time experiment video transmission, it is a key and difficult issue that the video is transferred across the network firewall in most of the current remote laboratory solutions. To address the network firewall issue, we developed a complete novel solution via HTTP Live Streaming (HLS) protocol and FFMPEG that is a powerful cross-platform command line video trans-code/encoding software package on the server side. In this paper, a novel, real-time video streaming transmission approach based on HLS for the remote laboratory development is presented. With this new solution, the terminal users can view the real-time experiment live video streaming on any portable device without any firewall issues or the need for a third party plug-in., This new solution also significantly benefits remote laboratory development in the future.